Pelanggaran Etika Pariwara Indonesia pada Akun Media Sosial Instagram @scarlettofficial - Wadkhulli Jannati Priyoko; Kaiza Nazwita Al Balqis; Daniel Handoko (Indo Publishing, 2025)
This research examines alleged violations of Indonesian Advertising Ethics (EPI) in advertisements uploaded to the Instagram social media account @scarlettofficial for the Scarlett Brightly Ever Afer Essence Toner product. The advertisement displays the claim